The Oretic Observation of the Cotton Movement in the Operating Camera of the New Separator - Makhkamov Mukhamatxonovich, Anvar; Khusanov Makhamatjonovich, Sadi; Rustam Muradovich, Muradov; Shokhsanam Fakhriddin Qizi, Imomaliyeva (International Journal of Psychosocial Rehabilitation, 2020)
The studies moving the pat product in its raw state in worker to camera of the separator to new design. The given article explored moving the pat-product in its raw state in worker-to-camera of the separator in new designs. Will Formed differential equation moving the pat and are received analytical decision, characterizing laws of motion from time.